Filantropi Nigeria dan Indonesia: Praktik Unggul serta Adopsi Budaya Memberi - Literature Review - Sofian Arisyandi (Universitas Andalas, 2026)
Indonesia and Nigeria both possess strong traditions of religious and communal giving, yet their philanthropic ecosystems are shaped by different socio-cultural and institutional dynamics. This article comparatively examines philanthropic practices in both countries and explores the contextual relevance of selected Nigerian philanthropic mechanisms for Indonesia. The study employs a qualitative comparative systematic literature review of publications indexed in Scopus and Google Scholar between 2015 and 2026. Using predefined inclusion criteria and a PRISMA-informed screening process, 50 publications were analyzed through thematic content analysis. The findings indicate that philanthropy in Nigeria is characterized by strong informal and community-based mechanisms, including diaspora remittance networks, rotating savings associations (esusu and ajo), place-of-worship-based redistribution, and technology-assisted accountability initiatives. In contrast, Indonesia demonstrates a more formalized philanthropic structure through zakat governance and faith-based institutions, although significant gaps remain between philanthropic potential and institutional participation. The study finds that differences in social capital, institutional trust, religious networks, and state–society relations shape philanthropic practices in both countries. While several Nigerian mechanisms exhibit contextual relevance for Indonesia, their adaptation requires alignment with local socio-cultural and institutional conditions. The study highlights the importance of hybrid philanthropic ecosystems that combine informal community participation with formal institutional accountability.